HIST1H1E syndrome with type 2 diabetes. Issue 7 (21st July 2021) - Ahmed, Mohammed S O; Rafey, Mohammed; McDonnell, Tara; Smith, Diarmuid
Abstract : A 20-year-old woman was referred to the diabetes clinic with type 2 diabetes diagnosed at the age of 19. Her body mass index was 31.4 kg/m 2, HbA1C was 76 mmol/mol, GAD antibodies were negative with a detectable C-peptide. She had a characteristic facial appearance with widespread eyes, posterior hairline suggesting a facial gestalt and abnormal dentition. She also had hypothyroidism, mild intellectual disability, primary amenorrhoea and patent ductus arteriosus. Karyotyping reported normal 46XX karyotype. Genetic testing revealed a pathogenic variant in the gene encoding the HIST1H1E protein which confirmed her diagnosis of HIST1H1E syndrome. Type 2 diabetes has not been reported in previous cases of HIST1H1E and so this is the first reported case of type 2 diabetes with HIST1H1E syndrome.